A massless boundary component mode synthesis method for elastodynamic contact problems. (February 2022) - Monjaraz Tec, C.D.; Gross, J.; Krack, M.
Highlights: Development of simulation method for dynamic contact problems. Combining ideas of mass redistribution and component mode synthesis. Reducing model order and spurious numerical oscillations. Excellent performance for frictionless and frictional benchmark problems. Computational speedup by several orders of magnitude. Abstract: We propose to combine the ideas of mass redistribution and component mode synthesis. More specifically, we employ the MacNeal method, which readily leads to a singular mass matrix, and an accordingly modified version of the Craig-Bampton method. Besides obtaining a massless boundary, we achieve a drastic reduction of the mathematical model order in this way compared to the parent finite element model. Contact is modeled using set-valued laws and time stepping is carried out with a semi-explit scheme. We assess the method's computational performance by a series of benchmarks, including both frictionless and frictional contact. The results indicate that the proposed method achieves excellent energy conservation properties and superior convergence behavior. It reduces the spurious oscillations and decreases the computational effort by about 1–2 orders of magnitude compared to the current state of the art (mass-carrying component mode synthesis method). We believe that the computational performance and favorable energy conservation properties will be valuable for the prediction of vibro-impact processes and physical damping.